Testing the effectiveness and/or appropriateness of the information material in The Alliance Programme used for Tshwana speaking patients suffering from schizophrenia in the South African context - Snyman, M.E. (Martha Elizabeth) (University of Pretoria, 2013)
Dissertation (MIS)--University of Pretoria, 2009.